Comprehensive Ergonomic Proposal for the Reduction of Musculoskeletal Risks in Soap Production: An Approach Based on Statistical Analysis and Postural Evaluation - Castro Rosales, Genesis Elizabeth; Torres Alvarado, Ashly Dayanna; Zalamea Cedeño, Luis Stalin; Duque-Aldaz, Francisco Javier; Rodríguez-Flores, Fernando Raúl (Ingeniería Química y Desarrollo, 2025)
In the soap production industry, workers face significant ergonomic risks due to repetitive tasks, load handling and forced postures, which can cause musculoskeletal injuries, fatigue and stress, affecting health and productivity. The objective of the research was to design a comprehensive ergonomic proposal to improve physical conditions and reduce ergonomic risks in the soap production line by identifying risks and developing practical solutions based on a comprehensive analysis. An initial diagnosis was made through ergonomic surveys and on-site observations. Responses were analyzed using standardized postural assessment methods and statistical tests (chi-square, Cramer's V, Lambda). The main ergonomic risks were identified and recommendations and practical solutions were formulated. The results showed that 67% of the workers reported maintaining forced neck postures for more than 2 continuous hours, and 58% of the trunk postures. Forty-two percent perform repetitive movements of the arms and wrists for more than 4 continuous hours, and 33% manually handle loads of more than 25 kg. In addition, 17% are exposed to vibrations and 25% to extreme temperatures. Lack of ergonomics training was reported by 100% of the workers. Statistical analyses revealed significant associations between ergonomic variables, providing a solid basis for the formulation of improvement proposals. The research confirmed the high prevalence of ergonomic risks in soap production, underlining the need for proactive ergonomic interventions to improve workers' health and productivity.
Keywords: Ergonomics; Ergonomic Risks; Musculoskeletal Disorders (MSD); Forced Postures; Repetitive Movements; Load Handling